2004
DOI: 10.1097/01.prs.0000124743.75839.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Outpatient Surgery Center Safety Using an Internet-Based Quality Improvement and Peer Review Program

Abstract: Assessing the quality of care delivered in office-based outpatient surgery centers is difficult because formerly there was no central data collection system. The American Association for Accreditation of Ambulatory Surgery Facilities (AAAASF), in its ongoing effort to assess and improve patient care, has developed an Internet-based quality improvement and peer review program to analyze outcomes for surgery centers it accredits. Reporting is mandatory for all surgeons operating in AAAASF-accredited facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 18 publications
(26 reference statements)
0
40
2
2
Order By: Relevance
“…The findings were encouraging with complication rates of less than 2%, suggesting that these facilities are safe for appropriately selected patients by qualified providers. [38][39][40][41] Soltani et al, in an analysis of outcomes on all procedures performed in American Association for Accreditation of Ambulatory Surgery Facilities (AAAASF) from 2001 to 2012, showed postoperative bleeding or hematoma to be the most common complication with a hospital admission rate of 0.2%. 42 Our data supports these findings with hematoma rates of 0.6% in office-based surgical suites and 1.0% in accredited surgical centers.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The findings were encouraging with complication rates of less than 2%, suggesting that these facilities are safe for appropriately selected patients by qualified providers. [38][39][40][41] Soltani et al, in an analysis of outcomes on all procedures performed in American Association for Accreditation of Ambulatory Surgery Facilities (AAAASF) from 2001 to 2012, showed postoperative bleeding or hematoma to be the most common complication with a hospital admission rate of 0.2%. 42 Our data supports these findings with hematoma rates of 0.6% in office-based surgical suites and 1.0% in accredited surgical centers.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Data from large studies on officebased surgery were able to quell some of the regulatory uncertainty and fear of widespread harm, noting complication rates of 0.3% to 1.5%. [6][7][8][9][10] Reported complication rates of ambulatory or office-based surgery often relate to the use of general anesthesia. Dermatologic surgery is generally performed using local or regional anesthesiasometimes including mild sedation-and therefore the inherent risk is minimized to an even greater degree.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 99%
“…28 -30 A recent study suggested that patient safety in outpatient surgery is highly correlated with American Association for Accreditation of Ambulatory Surgery Facilities certification and board certification of the operating surgeon. 31 Although several states do not require accreditation, the American Society of Plastic Surgeons and the American Society for Aesthetic Plastic Surgery recognize the importance of performing surgery in an accredited or state-licensed facility through a joint mandate of their members. 32 Professional self-regulation, such as the American Society of Plastic Surgeons Task Force on Patient Safety, may prove to be the most efficacious method of ensuring safety in outpatient or office-based surgery.…”
Section: Patient Safetymentioning
confidence: 99%